Between Sovereignty and Inclusion: Recognition of Customary Law in Constitutional Systems under International Supervision: Between Sovereignty and Inclusion: Recognition of Customary Law in Constitutional Systems under International Supervision - Jamhari Sugara; Muhammad Arya Wijaya; Alan Robert White (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
The recognition of customary law in constitutional systems creates normative and institutional tensions between state sovereignty and international oversight. Through a comparative study of five jurisdictions—Canada, Bolivia, South Africa, Indonesia, and New Zealand—this research explores how modern constitutions integrate customary law systems while maintaining compliance with global human rights standards and constitutional principles. Findings reveal diverse approaches, ranging from symbolic to substantive recognition, influenced by domestic political configurations and varying levels of international intervention. Using a theoretical framework of inclusive constitutionalism and interlegalism, this study argues that the coexistence of state law and customary law is not only possible but also crucial for democratic legitimacy and legal pluralism. This study contributes to the global development of constitutionalism through a conceptual framework that reconciles plural legal systems within a sovereign yet responsive constitutional design.